DESCRIPTION OF FOOD CONSUMPTION PATTERNS AND ANEMIA STATUS OF FEMALE STUDENT IN SMA NEGERI 1 KEDIRI,TABANAN - Ni Made Silya Niti Laksmi; I Made Suarjana; Desak Putu Sukraniti (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2020)
Anemia is a state of hemoglobin (Hb) in the blood lower than the normal value for groups of people according to age and sex. Nutritional anemia can be caused by a lack of nutrients that play a role in the formation of hemoglobin namely iron, protein, vitamin C. Based on Basic Health Research data (Riskesdas, 2013) there are 21.7% of the population with hemoglobin levels that are less than normal with a proportion of 20, 6% in urban areas and 22.8% in rural areas and 18.4% in males and 23.9% in females. The type of research is observational research with cross sectional design. This research was conducted at Kediri Tabanan 1 Public High School in February-May 2019 by searching for samples of 46 samples. The types of data collected include primary data on sample identity and secondary data, namely consumption patterns using the SQ-FFQ form. This study aims to describe the consumption patterns and anemia status female students Kediri 1 Public High School, Tabanan. Anemic status was based on the type of female food which was not as varied as 41.30% and varied 58.70%, anemia status based on the amount of protein consumption was less as much as 34.79% and good 65.21%, anemia status based on the amount of iron consumption less as much as 73.92% and good 26.08%, anemia status based on the amount of vitamin C consumption less as much as 53.65% and good 54.35%, anemia status based on frequency of use of female food ingredients in the category often as much as 73.91% and rarely 26.09%.Keywords: Consumption pattern, anemia, adolescence